The Capacity to Repair Sperm DNA Damage in Zygotes is Enhanced by Inhibiting WIP1 Activity - Leem, Jiyeon; Bai, Guang-Yu; Oh, Jeong Su (Frontiers in Cell and Developmental Biology, 2022)
Maintaining genome integrity in germ cells is essential not only for successful fertilization and embryo development, but also to ensure proper transmission of genetic information across generations. However, unlike oocytes, sperm are incapable of repairing DNA damage. Therefore, sperm DNA damage is repaired after fertilization in zygotes using maternal DNA repair factors. In this study, we found that zygotic repair of paternal DNA damage is enhanced by inhibiting WIP1 activity. Oxidative stress induced DNA damage in sperm and severely impaired motility. Although DNA damage in sperm did not compromise fertilization, it increased DNA damage in the paternal pronucleus of zygotes. However, WIP1 inhibition during fertilization reduced DNA damage in the paternal pronucleus, improving the rate of two-cell development, and subsequent zygotic genome activation. Therefore, our results suggest that WIP1 inhibition could enhance maternal DNA repair capacity and thereby decrease paternal DNA damage in zygotes.